ELF Whistler Dependence on a Sunlit Ionosphere. Issue 5 (2nd May 2018) - Fritz, Bruce A.; Heavisides, John; Young, Matthew A.; Kim, Hyomin; Lessard, Marc R.
Abstract: Narrow bandwidth, whistler‐like spectral features in the extremely low frequency (ELF) range were recorded at South Pole Station over the duration of 2004. A full year of observation shows a distinct lack of activity over the Antarctic winter season. A calculation of solar zenith angle at the time of detection illustrates a connection between the occurrence of ELF whistlers and a sunlit ionosphere. ELF whistlers detected at low latitude follow a similar general trend between ELF whistler occurrence rate and changing solar zenith angle, but with an additional persistence of detections after local sunset. Temporal profiles from the International Reference Ionosphere 2016 show that the peaks in ELF whistler occurrence align with times of changing ionospheric composition. Correlation with solar activity per the F 10.7 index shows no connection to daily variations in activity, and the consistency of solar flux levels throughout 2004 appears insufficient to explain the absence of events during the winter blackout. These observations place new physical constraints on the conditions necessary for detecting ELF whistlers and suggest the potential for localized generating mechanisms due to plasma instabilities in the ionosphere. Key Points: ELF whistlers are detected at the South Pole only when the local ionosphere is sufficiently sunlit Peak occurrence times of ELF whistlers align with times of composition change in the local ionosphere Daily solar flux levels do not correlate with daily occurrence rate of ELF whistlers